Modelling and simulation for high speed optical fiber receiver performance analysis - Dubey, Vimal Kishore. (2008)
This report describes a model suitable for simulation of optical fiber communication system for transmission of digital data. The model is based on the idea of defining the spectral function for each of the sub-system like transmitter, fiber and receiver.